Calcium pyrophosphate crystal deposition disease as a risk factor for cardiovascular diseases - A. M. Novikova (Научно-практическая ревматология)
Calcium pyrophosphate crystal deposition disease (CPPD) is an inflammatory joint disease associated with abnormal accumulation of inorganic pyrophosphate. CPPD is frequently associated with metabolic disorders, such as hyperparathyroidism, hemochromatosis, hypomagnesemia, and hyperphosphatasia. It is important that pathological calcification can develop in both the joints and vessel wall. It is assumed that the deposition of calcifications in the endothelium, the crystal-induced chronic inflammation characteristic of CPPD, and its accompanying oxidative stress, as well as metabolic disorders that are a cause of secondary CPPD, can significantly increase the risk of cardiovascular diseases.